(3eONd cejs - (3HdGd(B, (3eMeO GSeGYjds ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2004)
(3eaGgje CSGSjI, JNWjW GdfTGW GdGfJGLj(B: (3JNWjW GdfTGW GdGfJGLj, GdJfHD HGdWdH, GNJjGQ ehbY GdeTQhY, JfXje GdfTGW GdGfJGLj(B: (3GdYhGed GdeDKQI aj JfXje GdfTGW GdGfJGLj, JUeje GdNW GdGfJGLj, GdLOhdI, GdQbGHI aj eLGd GdGfJGL hGdYedjGJs
(3GdeQGLY U(B.397s
Keywords: (3EOGQI GdEfJGLs; (3GdGfJGL(B-(3JNWjWs; (3GdQbGHIs; (3GdcaGjI GdEfJGLjIs; (3HMhK GdYedjGJs